LEGAL – HISTORICAL OVERVIEW OF THE PROTECTION OF HOMESTEAD (FARMER´S MINIMUM) IN SERBIAN LAW - Gavrilović, Biljana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The subject of this analysis is the protection of homestead (farmer´s minimum), from when it was introduced into Serbian law until the Second World War. The regulation about prohibiting debt collection of the peasant cover the essential part of his homestead, was introduced into Serbian law in the year 1836. It was necessary to prescribe the protection of the homestead, because the peasants borrowed from the usurers and thus lost their house and the last piece of land. That protection of the farmer´s house and a few days of land became an integral part of Serbia´s legal identity. The regulation about prohibiting debt collection of the peasant cover the essential part of his homestead did not exist in all parts of the Kingdom of Serbs, Croats and Slovenes. Because of that, when the Kingdom of Serbs, Croats and Slovenes was founded, the unification of laws became a priority task of the government. In this regard, a rich debate developed, which lasted until the Second World War.